2018
DOI: 10.1111/clr.13311
|View full text |Cite
|
Sign up to set email alerts
|

Implant supported cantilevered fixed dental rehabilitations in partially edentulous patients: Systematic review of the literature. Part I.

Abstract: Objectives To investigate in which clinical situations a cantilever fixed implant supported restorations can be a treatment alternative and which complications are reported. Materials and Methods Two operators screened the literature (MEDLINE, EMBASE) and performed a hand search on the main journals dealing with implantology and prosthetics until 31 December 2017. Only articles that considered cantilever implant fixed restorations with at least 10 patients and with a mean follow‐up of at least 5 year were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 114 publications
1
37
2
2
Order By: Relevance
“…Compared with the longitudinal survival rates of each prosthesis reported in other studies, our six-year cumulative survival rates in the IFD and FPD groups in this study were similarly high [12][13][14][15]. However, the survival rate in the RPD group was lower than those reported in previous studies [16][17][18].…”
Section: Discussioncontrasting
confidence: 58%
“…Compared with the longitudinal survival rates of each prosthesis reported in other studies, our six-year cumulative survival rates in the IFD and FPD groups in this study were similarly high [12][13][14][15]. However, the survival rate in the RPD group was lower than those reported in previous studies [16][17][18].…”
Section: Discussioncontrasting
confidence: 58%
“…High survival rates of implant-supported FDPCs were reported both in prospective and retrospective studies (Storelli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Storelli et al found that the use of a cantilever can be a successful treatment option in partially edentulous patients, with a complication rate of 26.6% over observation periods of 5-10 years; however, treatments using single-tooth implants with cantilevers have not been sufficiently documented to produce any clear conclusion [50]. Providing the clinical situation permits, treatments using a splinted extra-short implant instead of a cantilever it could offer a viable alternative, as the present work observed no short-term prosthetic or biological complications.…”
Section: Discussionmentioning
confidence: 99%